Lactobacillus garvieae endocarditis presenting with leg cramps. (2018) - Lim, Seok Mei; Wong, Beatrix; Cross, Gail Brenda; Merchant, Reshma
Highlights: Not all elderly people with leg cramps only have degenerative disc disease. Consider atypical presentations in elderly patients when clinical progression is not befitting initial diagnosis. Lactococcus garvieae is an increasingly recognized zoonotic pathogen in elderly and immunosuppressed individuals. Abstract: An 85-year-old man with a history of aortic valve replacement presented with lower limb cramps. He was initially diagnosed with degenerative disc disease, but was found to have Lactococcus garvieae infective endocarditis with septic embolic strokes causing a central poststroke pain syndrome. Cardiothoracic surgery was deemed too high risk and the patient completed 6 weeks of intravenous antimicrobials as well as prolonged inpatient rehabilitation. Lactococcus garvieae is an aquaculture pathogen which typically affects elderly and immunocompromised patients. Atypical presentations of endocarditis in the elderly can lead to delays in diagnosis.